2000
DOI: 10.1111/j.0014-3820.2000.tb00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic Patterns and High Levels of Chloroplast Dna Diversity in Four Packera (Asteraceae) Species in Southwestern Alberta

Abstract: Abstract. Chloroplast DNA (cpDNA) haplotype variation is compared among alpine and prairie/montane species of Packera from a region in southwestern Alberta that straddles the boundary of Pleistocene glaciation. The phylogeny of the 15 haplotypes identified reveals the presence of two groups: one generally found in coastal and northern species and the other from species in drier habitats. The presence of both groups in all four species and most populations from southwestern Alberta is evidence of past hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…The congruence in pattern between char and plants suggests that historical processes have strongly impacted not only the phylogeographic distribution of intraspecific lineages in diverse taxa, but also evolutionary interactions between species such as introgression. In particular, these analogous situations highlight the potential role of the dynamic geological history of northwestern North America in initiating vicariance and influencing dispersal patterns and subsequent evolutionary interactions between species (see also Latta and Mitton 1999;Golden and Bain 2000). Phillips et al (1999) showed (with rDNA sequences) that Dolly Varden were paraphyletic with respect to Arctic char.…”
Section: Historical Introgression and Reticulate Evolution In Charmentioning
confidence: 94%
“…The congruence in pattern between char and plants suggests that historical processes have strongly impacted not only the phylogeographic distribution of intraspecific lineages in diverse taxa, but also evolutionary interactions between species such as introgression. In particular, these analogous situations highlight the potential role of the dynamic geological history of northwestern North America in initiating vicariance and influencing dispersal patterns and subsequent evolutionary interactions between species (see also Latta and Mitton 1999;Golden and Bain 2000). Phillips et al (1999) showed (with rDNA sequences) that Dolly Varden were paraphyletic with respect to Arctic char.…”
Section: Historical Introgression and Reticulate Evolution In Charmentioning
confidence: 94%
“…This area has also been cited as a core region for the hybrid origin of some pine species and varieties (Styles 1993). In this scenario, it is also expected that we will find similar chloroplasts in closely related species because of hybridization and/or the retention of ancestral polymorphisms (Golden and Bain 2000). These two phenomena could be in some instances dissociated through the analysis of the geographic distribution of the putative hybrids and their position in a haplotype network.…”
Section: Introductionmentioning
confidence: 97%
“…In others, earlier hybridization during glacial periods has been inferred. For instance, cpDNA diversity in northern populations of Packera pseudaurea (Asteraceae) in Alberta suggests former hybridization with other Packera species that migrated southwards during periods of glaciation (Yates et al 1999;Golden & Bain 2000). In southeast Spain, species of Armeria (Plumbaginaceae), which now occur at different altitudes, may have hybridized during Quaternary compressions of vegetation within massifs (Larena et al 2002).…”
Section: Discussionmentioning
confidence: 99%